Finding the Guardians of Royal Blood: Observations on the Supply of eunuchs to the Harem in the Ottoman Empire and the Crimean Khanate through case studies and documents - Ürkündağ A.; Başer A. (Золотоордынское обозрение)
Research objectives: The first aim of this study, which deals with the supply process of the eunuchs, who formed the backbone of the harem organization in the Ottoman Empire and the Crimean Khanate, is to determine how the career of the eunuchs began in the palace of the sultan or the khan. Research materials: The main sources of data for this research are documents held within the Department of Ottoman Archives of the Presidency of the Republic of Turkey Directorate of State. Upon these documents, Ottoman and Crimean chronicles of the period were examined and evaluated. Research and novelty of the research: Both the Ottoman Empire and the Crimean Khanate established harem organizations and started employing eunuchs soon after the foundation of the state. These people, who were called eunuchs or castrates and had lost their masculinity due to natural or unnatural causes, were the backbone of the harem organization. It was found that the main method for supplying eunuchs to the harem was purchasing them from specialized merchants. Both states made efforts to identify children who had lost their masculinity due to natural causes and employ them in the harem. More over, in a very rare event in Ottoman history, Gazanfer and Cafer Aghas volunteered to be castrated out of a desire to be close to the Sultan during the reign of Selim II. The Ottoman administration paid special attention to social as well as physical characteristics of the eunuchs to be employed, and, for example, preferred that they learn Turkish in the Ottoman harem, under their own supervision. It was also observed that the Crimean Khanate attached great importance to the harem organization as in the Ottoman Empire. However, it has been revealed that the institutionalization in the harem organization was underdeveloped than in the Ottoman harem and that at least some of the eunuchs were part of the khan’s entourage and moved away from the palace when the khan was dethroned. It’s also been revealed that sometimes the information in the primary sources contradicts with the documents produced by the bureaucracy of the period. It’s been determined that a special emphasis was placed on the shaping of the eunuchs with the Ottoman high culture, and those who somehow lost their manhood, even if they were Muslims, lost their individual identity and were transformed into an officer belonging to the state.